Adapting to extremes: Reconstructing evolution in response to changing climate over time and space in the diverse Australian plant genus Acacia. (15th March 2022) - Hua, Xia; Cardillo, Marcel; Bromham, Lindell
Abstract: Aim: Macroevolutionary analysis is increasingly being used to study biodiversity responses to climate change, for example by using phylogenetic node ages to infer periods of diversification, or phylogenetic reconstruction of traits to infer adaptation to particular stresses. Here we apply a recently developed macroevolutionary method to investigate the responses of a diverse plant genus, Acacia, to increasing aridity and salinity in Australia from the Miocene to the present. We ask whether increase in tolerance of aridity and salinity coincided with periods of aridification, and if it allowed the radiation of Acacia into a wide range of niches. Taxon: Acacia. Location: Australia. Methods: We applied the Niche Evolution Model (NEMo), which combines environmental (or ecological) niche modelling (ENM) with phylogenetic comparative methods (PCMs) in a single statistical framework, to a large database of Acacia presence‐only records and presence–absence survey sites in order to infer current environmental tolerances of Australia Acacia species and reconstruct the evolution of environmental tolerance to increasing aridity and salinity. Results: We find that patterns in evolution of Acacia, over time and across different habitat types, are consistent with the aridification history of Australia and suggests substantial ability to adapt to high aridity and salinity. Main conclusions: Our results suggest that many Acacia lineages have been able to exploit new environments created during the aridification of Australia through evolution of environmental tolerance, resulting in their current dominance of many habitats across the continent. This study demonstrates that phylogenetic studies of the evolution of responses to changing environment can move beyond the application of simple trait‐based models, allowing the underlying processes of speciation, adaptation and dispersal to be explicitly modelled in a macroecological and macroevolutionary context.